INTEGRATION OF “WRITE AND IMPROVE” AWE TOOL INTO EFL AT HIGHER EDUCATIONAL ESTABLISHMENT: CASE STUDY - Kateryna Karpova (University of Muhammadiyah Malang, 2020)
Dramatic changes in political, economic, cultural, scientific, and technological spheres, which have taken place in recent decades, have caused noticeable alterations in different societal domains, including education. Through the prism of the modern educational paradigm that mainly focuses on meeting the needs of human beings, nowadays, a special place is occupied by ICTs and their integration into the educational process. The present research is devoted to both theoretical evidence and practical implementation of automated writing evaluation (AWE) tool “Write and Improve” into language learning at a higher educational establishment. We use experimental method titled case study, which allows finding out ways to incorporate the software mentioned above into EFL. First and foremost, the author analyses fundamental and contemporary studies in the realm of ICT integration into language teaching, learning, and assessment. Special attention is paid to AWE as cutting-edge software, which utilizes artificial intelligence to assess students’ writing. The data under investigation indicate that using AWE computer-assisted programs facilitates students’ management and increases motivation for writing and revision. The article sets a goal to demonstrate that “Write and Improve” is an example of innovative technology to enhance writing as an essential academic competency. Based on profound theoretical substantiations, the author conducts the experiment to test the research hypothesis in the case study. Within the framework of the article's written tasks, university students who study English as their major subject at the Taras Shevchenko National University of Kyiv have been chosen. The attempted investigation proved “Write and Improve” to be highly effective among language learners, thus worth being introduced not only into teaching and learning but also assessment.